Expression patterns and prognostic value of N6-methyladenosine regulators in esophageal cancer - Xinhua Xu; Changchun Lai; Hao Chen; Runkun Han; Xiaobin Wu (Eurasian Journal of Medicine and Oncology, 2026)
Introduction: Aberrant m6A regulators contribute to esophageal cancer, yet few studies stratify by subtype and compare prognostic models. Objectives: N6-methyladenosine (m6A) modification broadly regulates cancer progression and prognosis, while its clinical role in esophageal cancer (EC) remains poorly defined. Methods: Based on The Cancer Genome Atlas data, we analyzed 13 m6A regulators in EC and normal tissues, and constructed a prognostic signature using Cox and least absolute shrinkage and selection operator (LASSO) regression analyses. Model performance was validated using C-index and time-dependent receiver operating characteristic curves and compared with tumor–node–metastasis (TNM) staging and existing models. Results: Eight m6A regulators (METTL3, KIAA1429, YTHDC1, HNRNPC, WTAP, RBM15, YTHDF1, YTHDF2) were significantly upregulated in EC tumors, with YTHDC1 showing the strongest correlation with METTL14 (r = 0.55). A four-gene m6A-regulator expression signature was identified using LASSO Cox regression. Both univariate and multivariate Cox analyses revealed that the risk score and TNM stage were independent risk factors. High-risk patients had worse overall survival (OS) across all stages and subtypes. Low-risk stage I–II patients had better OS. Combining the risk score with TNM stage improved prognostic accuracy over TNM stage alone, though differences with the risk score model were not significant. Our risk model was particularly effective at predicting 1-year OS, whereas TNM staging and other signatures were better at predicting 3- and 5-year survival. Conclusion: We explored the role of m6A in EC and created a four-gene m6A-regulator expression signature risk model that serves as an independent prognostic biomarker, complementing TNM staging to aid in personalized postoperative care for EC patients.